(untitled) (Journal of Scientific Research, 2016)
The present paper is an investigation of steady MHD free convection, heat and mass transfer flow of an incompressible electrically conducting fluid over a stretching sheet in a rotating system under the influence of an applied uniform magnetic field with Hall current. The governing equations are transformed to a system of non-linear ordinary differential equations which are then solved numerically by the shooting method. The numerical results concerned with the primary velocity, secondary velocity, temperature and concentration profiles, effects of various parameters on the flow fields are investigated and presented graphically. The results presented graphically illustrate that primary velocity field decrease due to increase of rotational and magnetic parameter but reverse results arises in case of Hall and heat generation parameter while secondary velocity decrease for stretching parameter and increase for Hall, rotational and magnetic parameter. The thermal boundary layer decreases for the increasing values of mentioned parameter. Also, concentration profiles decreases for increasing the values of magnetic parameter, rotational parameter, reaction parameter and Schmidt number but increases for heat generation and Dufour number. Finally, the numerical values of the skin friction, wall temperature gradient and concentration gradient are also shown in a tabular form.